2019
DOI: 10.1080/00131881.2018.1562954
|View full text |Cite
|
Sign up to set email alerts
|

Using a video app as a tool for reflective practice

Abstract: This is a self-archived version of an original article. This version usually differs somewhat from the publisher's final version, if the self-archived version is the accepted author manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…Indeed, despite these somewhat pessimistic views of technology by both Ingold [ 12 ] and Malpas [ 15 ], it is important to note that it can support and actually promote positive behavioural change in certain instances [e.g. 3 , 16 ]. Our point, however, is that there are many unquestioned assumptions and consequences of the technological trend to replace and intervene in direct human perception–action interactions with the environment—some of which we discuss here.…”
Section: A (Brief) Philosophical Excursionmentioning
confidence: 99%
“…Indeed, despite these somewhat pessimistic views of technology by both Ingold [ 12 ] and Malpas [ 15 ], it is important to note that it can support and actually promote positive behavioural change in certain instances [e.g. 3 , 16 ]. Our point, however, is that there are many unquestioned assumptions and consequences of the technological trend to replace and intervene in direct human perception–action interactions with the environment—some of which we discuss here.…”
Section: A (Brief) Philosophical Excursionmentioning
confidence: 99%
“…In online supervision, pre-service teachers bring their experiences into the supervising discussion and the focus is on promoting pre-service teachers' reflection process (cf. Körkkö, Morales Rios, & Kyrö-Ämmälä, 2019). Therefore, a supervisor must have adequate skills to guide pre-service teachers to notice integral aspects in their teaching to support their learning from experiences.…”
Section: Discussionmentioning
confidence: 99%
“…In teacher education, video recordings of demonstrations and practice performances allow students to observe and reflect on their professional practices (Calandra & Rich, 2015;Coffey, 2014;Colasante, 2011;Gaudin & Chaliès, 2015;Hamel & Viau-Guay, 2019;Körkkö et al, 2019;van Es et al, 2017;Zhang et al, 2011).…”
Section: Using Video and Video Annotation In Teacher Educationmentioning
confidence: 99%
“…Reflections on teaching practices and assessment for learning (AfL) are important for fostering teacher professionalism in teacher education (Schön, 1983(Schön, , 1987. Peer feedback is a central element of AfL (Black & Wiliam, 1998;Kluger & DeNisi, 1996), and the use of videos and video annotation may enhance student teachers' critical reflections on their teaching practices (Calandra & Rich, 2015;Coffey, 2014;Colasante, 2011;Gaudin & Chaliès, 2015;Hamel & Viau-Guay, 2019;Körkkö et al, 2019;van Es et al, 2017;Zhang et al, 2011). In 2006, Butler et al suggested that educators should use video annotation to provide formative feedback on transient events, such as professional training or oral presentations, because video recordings and annotation anchor comments to specific parts of a practical performance.…”
Section: Introductionmentioning
confidence: 99%